MEDIA INFORMASI DAN PENGETAHUAN TENTANG MAKANAN PENDAMPING ASI - Suci Fitriana Pramudya wardani (Journal of Midwifery and Health Administration Research, 2023)
Background: Complementary foods are nutritious foods or drinks given to children aged 6-24 months to meet nutritional needs other than breast milk. Proper and good Complementary foods is a food that is able to meet the nutritional needs of children and is good for growth and development. The purpose of this study was to examine the impact of the use of information media to increase maternal knowledge about Complementary foods. Method: The type of research used in this study is experimental research with a Quasi-Experimental approach (Pseudo-Experiment) presented in Non-equivalent Control Group Design. The research was conducted in Karanglo Village, Brebes Regency. The sample of this study amounted to 32 people. Data analysis using Wilcoxon Sign Rank Test. Results: the results showed that there was an increase in knowledge for the better in the treatment group as many as 15 respondents (93.8%) and in the control group as many as 7 respondents (43.8%). The results of the influence test using the Wilcoxon test showed that there was an increase in knowledge with p values of 0.000 < 0.05 in both the treatment group and the control group, so there was an influence of counseling on the provision of Complementary foods on the knowledge of breastfeeding mothers. Conclusion: There is an influence of the use of information media on increasing maternal knowledge about Complementary foods. Health workers are expected to be able to utilize existing information media to increase public knowledge about complementary foods.